Perancangan Website dan Aplikasi Mobile Untuk Kontrol Jarak Jauh Pada Sistem Smart Gate Perumahan - Luthfi Abdul Hafizh; Sony Sumaryo; Muhammad Ary Murti (Jurnal Serambi Engineering, 2024)
The Internet of Things (IoT) technology has brought significant changes in various aspects of life, especially in the field of security and access control. This research aims to design and develop an IoT-based remote gate control system, integrated with a website and mobile application, with a focus on implementation in residential areas. The system will allow residents to control the gate from anywhere at any time using internet connected devices, while visitors will be able to request access through the website without the need to install any application. In this study, the system architecture includes servers, hosting services, databases and hardware components such as sensors and gate actuators. The test results show that the system works with excellent accuracy, reaching 100% on both the website and the mobile application, with no errors in the access request process. The results of this research indicate that the developed system provides a practical and efficient solution for managing access to residential gates, and can also be adapted to other environments such as office buildings and public facilities.